Analysis of feed pelleting characteristics based on a single pellet press device - Peng, Fei; Xiang, Rui; Fang, Fang; Liu, Dan (International Journal of Agricultural and Biological Engineering, 2022)
Pelleting is the most extensively used thermal processing method in feed industry. In this article, a single pellet press device was developed to investigate the pelleting processing of animal feed. Effects of moisture content (10%-18% w.b.), preheating temperature (60°C-100°C) and maximum compression force (0.2-0.6 kN) on feed pellet were determined and analyzed, as well as energy consumption. The results showed that unit density, pellet hardness and energy consumption were 0.87-2.92 g/cm3, 1.08-4.55 kg, and 3.27-12.66 J/g, respectively. Unit density was found to increase with the increase of preheating temperature and maximum compression force, but decrease with the increase of moisture content. Pellet hardness showed a first ascending then descending trend with the increase of moisture content, but exhibited a positive relationship with both preheating temperature and maximum compression force. Energy consumption increased with the increase of maximum compression force, but exhibited descending trends with the increase of moisture content and preheating temperature. Due to its features of low cost, high efficiency and easy control, the single pellet press device has a wide application prospect in feed processing.Keywords: feed, pelleting, energy consumption, preheating temperature, experimentsDOI: 10.25165/j.ijabe.20221504.6155Citation: Peng F, Xiang R, Fang F, Liu D. Analysis of feed pelleting characteristics based on a single pellet press device. Int J Agric & Biol Eng, 2022; 15(4): 65–70.